Organisation of care for pregnancy in patients with congenital heart disease. Issue 23 (24th July 2017) - Roos-Hesselink, Jolien W; Budts, Werner; Walker, Fiona; De Backer, Julie F A; Swan, Lorna; Stones, William; Kranke, Peter; Sliwa-Hahnle, Karen; Johnson, Mark R
Abstract : Improvements in surgery have resulted in more women with repaired congenital heart disease (CHD) surviving to adulthood. Women with CHD, who wish to embark on pregnancy require prepregnancy counselling. This consultation should cover several issues such as the long-term prognosis of the mother, fertility and miscarriage rates, recurrence risk of CHD in the baby, drug therapy during pregnancy, estimated maternal risk and outcome, expected fetal outcomes and plans for pregnancy. Prenatal genetic testing is available for those patients with an identified genetic defect using pregestational diagnosis or prenatal diagnosis chorionic villus sampling or amniocentesis. Centralisation of care is needed for high-risk patients. Finally, currently there are no recommendations addressing the issue of the delivery. It is crucial that a dedicated plan for delivery should be available for all cardiac patients. The maternal mortality in low-income to middle-income countries is 14 times higher than in high-income countries and needs additional aspects and dedicated care.